Imagining transformation: Change agent narratives of sustainable futures. (September 2022) - Riedy, Chris; Waddock, Sandra
Abstracts: Deliberate transformation for sustainable futures requires new social imaginaries that collectively envision futures beyond the dominance of neoliberal capitalism. We looked for these imaginaries by surveying change makers working on system transformation and ecological issues. Drawing on a conceptual framework that connects social imaginaries, stories and memes, our research asked: what are the memes and stories that proponents of transformation use to describe desirable futures? And, how likely are social imaginaries derived from these memes and stories to guide deliberate transformation? Collectively, the 72 survey respondents valued ideas of harmony with nature, social justice and equality, ecological sustainability, human awakening, compassion, wellbeing, and connection as elements of their imagined futures. Many found it difficult to then incorporate these ideas into stories. Nevertheless, they identified three simple plot devices for moving from a problematic present to their desired future – crisis, 'waking up' and collective action through social movements. Overall, social imaginaries formed from these stories and ideas are contested and currently lack the plausibility and tangibility to challenge neoliberal capitalism. Transformative social imaginaries could grow from these ideas if change agents nurture shared visions of desirable futures, explore real practices that support awakening and create tangible stories to guide collective action by 'all of us'. Highlights: New social imaginaries are needed to guide deliberate transformation for sustainable futures. An online survey of change agents working on transformation found imaginaries that lack plausibility and tangibility. Visions for the future were consistent and valued cooperative relationships with nature and other people. Theories of change were variations of crisis, awakening and collective action. The shared vision and ideas of awakening and collective action offer hope for nurturing transformative social imaginaries.